Attitudes toward genetic testing and personalised nutrition in a representative sample of European consumers - Knox, Barbara Stewart (2009)
Negative consumer opinion poses a potential barrier to the application of nutrigenomic intervention. The present study has aimed to determine attitudes toward genetic testing and personalised nutrition among the European public. An omnibus opinion survey of a representative sample aged 14-55+ years (n 5967) took place in France, Italy, Great Britain, Portugal, Poland and Germany during June 2005 as part of the Lipgene project. A majority of respondents (66 %) reported that they would be willing to undergo genetic testing and 27 % to follow a personalised diet. Individuals who indicated a willingness to have a genetic test for the personalising of their diets were more likely to report a history of high blood cholesterol levels, central obesity and/or high levels of stress than those who would have a test only for general interest. Those who indicated that they would not have a genetic test were more likely to be male and less likely to report having central obesity. Individuals with a history of high blood cholesterol were less likely than those who did not to worry if intervention foods contained GM ingredients. Individuals who were aware that they had health problems associated with the metabolic syndrome appeared particularly favourable toward nutrigenomic intervention. These findings are encouraging for the future application of personalised nutrition provided that policies are put in place to address public concern about how genetic information is used and held.